Efecto de aceites esenciales en emulsión, en el control de mosca blanca (Trialeurodes vaporariorum), en condiciones de laboratorio, provincia de Cotopaxi, cantón Latacunga - Pallasco Chilla, Fausto Elian (2023)
The present investigation was carried out in the Entomology laboratory of the Technical University of Cotopaxi, the control of two essential oils (Ruta graveolens and Anethum graveolens) was evaluated in emulsion at two concentrations of 25% and 50%, including the control and Tween 80. for the control of Trialeurodes vaporariorum. A Completely Random Design (DCA) was applied with an A*B factorial arrangement with nine treatments and three repetitions and a total of 27 experimental units, in each experimental unit 100 individuals of Trialeurodes vaporariorum were released, in which the oils were applied. essential in emulsion. Mortality data collection was performed by observation from the moment of application, obtaining data at min, 2 min, 3 min and 4 min, using the count and extraction of dead individuals. In addition, the chemical composition was analyzed through gas chromatography coupled to a mass spectrometer detector in the Agilent Technologies 5975C inert XL MSD with Triple - Axis Detector equipment where various organic compounds were appreciated, with a greater presence of 2-un decanone with 46.88% in Ruta graveolens and Alfa-Tijone with 10.44% in Anethum graveolens. It is concluded that the essential oils in emulsion control Trialeurodes vaporariorum under laboratory conditions with an average of 36.44 dead individuals of Ruta graveolens followed by 27.33 dead individuals of Anethum graveolens. The interaction between oils*concentrations, Ruta graveolens in a 50% concentration presented an average of 68.33 dead individuals one minute after the application of the oil in emulsion.